White Spot Disease in Black Tiger Shrimp (Penaeus Monodon Fab.) : Infection of White Spot Virus at 20, 100 and 200 uG/Ml by Dipping Method within 120 Minutes Exposure Time - Alifuddin, M.; Dana, D.; Eidman, M.; Malole, M.B.; Pasaribu, F.H. (Indonesian Society of Scientific Aquaculture (ISSA), 2003)
An infection trial of white spot disease on tiger shrimp was conducted by water borne inoculation with the different of viral concentration. The result showed that the viral concentration influenced the appearance of white spot specific lesion, occurrence and disease development. This study also indicated that white spot virus infect hepato-pancreatic tissue as well as gill, intestine and lymphoid tissues. Key word: White spot virus, infectious disease, tiger shrimp, Penaeus monodon Fab. ABSTRAK Percobaan penularan penyakit white spot pada udang windu telah dilakukan secara perendaman dengan berbagai konsentrasi virus. Hasil percobaan ini memperlihatkan, bahwa konsentrasi virus mempengaruhi kemunculan lesi spesifik penyakit white spot, kejadian dan perkembangan penyakit. Percobaan ini juga memperlihatkan, bahwa hepatopankrea terserang virus white spot disamping, insang, usus dan jaringan limfoid. Kata kunci: Virus white spot, penyakit infeksi, udang windu, Penaeus monodon Fab.